A-bomb : a city tells its story - Kosakai, Toshiteru (Hiroshima: Hiroshima Peace Culture Center, 1972)
"Compiler : Yoshiteru Kosakai ; Translated by : Kiyoko Kageyama, Charlotte Susu-Mago, Kaoru Ogura"